A solitary blue - Voigt, Cynthia (New York : Simon Pulse, 2003)
Jeff's mother, who deserted the family years before, reenters his life and widens the gap between Jeff and his father, a rift that only truth, love, and friendship can heal.
Newbery Medal/Honor.
Wilson's Junior High School.
Wilson's Senior High School.
Kirkus Review, June 2000.
Notable/Best Books (A.L.A.), January 2010.
Wilson's Junior High School, January 2010.
Keywords: Divorce -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Divorce -- Fiction; Fathers and sons -- Fiction; Divorce -- Fiction; Father-son relationship -- Fiction